The Influence of Influencer Endorsement, Content Marketing, and Live Streaming on Online Shop Sales Turnover in Palembang City - Dela Veranda; Trisninawati; Septiani Fransisca; Rahma Santhi Zinaida (CV. Doki Course and Training, 2026)
Objective:This study aims to analyze the influence of influencer endorsements, content marketing, and live streaming on sales turnover of online shops in Palembang City. The rapid growth of e-commerce is encouraging businesses to adopt digital marketing strategies that can improve competitiveness and sales performance. Method:This study employed a quantitative approach with a survey method. Primary data were obtained by distributing questionnaires to online shop owners in Palembang City, selected using a purposive sampling technique. Data analysis was performed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method using SmartPLS software. The conceptual framework of this study refers to the Theory of Planned Behavior (TPB), where influencer endorsements, content marketing, and live streaming are positioned as stimuli that influence consumer responses in the form of increased sales turnover. Results :The results of the study indicate that influencer endorsements have a positive and significant effect on sales turnover, content marketing has a positive and significant effect on sales turnover, and live streaming has a positive and significant effect on sales turnover for online shops in Palembang City. Simultaneously, influencer endorsements, content marketing, and live streaming were proven to have a significant effect on increasing sales turnover. Originality (Novelty)- Streaming has been shown to significantly increase sales turnover. This finding indicates that implementing appropriate, credible, and interactive digital marketing strategies can improve the sales effectiveness of online shop businesses. Implications –This research is expected to serve as a practical reference for business actors in designing digital marketing strategies, as well as being an academic contribution to the development of social commerce-based digital marketing studies.